«ШӘРИЯР» ДӘСТАНЫН ОҚЫТЫЎ АРҚАЛЫ ТӘЛИМ-ТӘРБИЯНЫҢ НӘТИЙЖЕЛИЛИГИН АРТТЫРЫЎДА ОҚЫТЫЎ ФОРМАЛАРЫНЫҢ ТУТҚАН ОРНЫ (Конференция ҳәм пикирлесиў-диспут сабағы формалары мысалында) - Алламбергенов, Е.К. (SCIENCE and SOCIETY, 2020)
The given article deals with innovative technologies more over advantage of using interactive methods at the lessons. The author presents using interactive methods in teaching literature with materials and topic "Shariyar" dastan, «such as» «corners» method, IREC technology.